Angiosarcoma Arising in a Patient with a 10-Year-Old Hemangioma. (31st December 2014) - Nathenson, Michael J.; Molavi, Diana; Aboulafia, Albert
Abstract : The transformation of a benign hemangioma into a malignant angiosarcoma has been rarely reported, with only 11 cases reported in the literature. There have been no reports of malignant transformation of hemangioma into angiosarcoma in association with epithelioid hemangioendothelioma, to our knowledge. The existence of precursor malignancies in the tumorigenesis of sarcomas is still not clearly defined. We describe the case of a 40-year-old woman with a preceding history of a suspected hemangioma for ten years, who upon resection was found on histology to have evidence of a hemangioma with an associated area of epithelioid hemangioendothelioma as well as areas of overt high grade epithelioid angiosarcoma. These findings raise the possibility of the evolution of hemangioma to epithelioid hemangioendothelioma, and the latter to overt angiosarcoma. The patient was managed as having a high grade sarcoma with wide resection and radiation. She declined systemic adjuvant chemotherapy after a thorough discussion about the risks and benefits of chemotherapy, and she currently remains disease free one year after the surgery.